US hackers target student databases to steal identities. - Marcus, Jon (Times Higher Education Supplement, 2005)
Reports on the proliferation of identity theft and computer hacking in universities in the U.S. Prevalence of computer crimes whereby hackers steal students' personal information to obtain credit illegally; Victims of identity theft; Crime costs.